Personnel Administration Based on the Four Sublime States of Mind of School Administrators under the Chanthaburi Primary Educational Service Area Office 2 - หาจันดา, นวเมษฐ์; การีเวท, สมนึก (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to examine, compare, and explore guidelines for developing personnel administration based on the Four Sublime States of Mind of school administrators under the Chanthaburi Primary Educational Service Area Office 2. The sample consisted of 299 school administrators and teachers. The research instrument was a questionnaire on personnel administration based on the Four Sublime States of Mind in four aspects: loving-kindness, compassion, sympathetic joy, and equanimity. The statistical methods used for data analysis included percentage, mean, standard deviation, t-test, and F-test. The questionnaire was try-tested with a sample of 30 respondents to determine reliability using Cronbach’s alpha coefficient (Cronbach, L. J, 1990) which yielded a reliability value of greater than 0.70 indicating that the instrument was reliable for data collection.          The results revealed that: 1. Overall, personnel administration based on the Four Sublime States of Mind was rated at a high level (x̄= 4.24, S.D. = 0.381) according to the opinions. When considering each aspect, compassion (karuna) received the highest mean score and was rated at a high level (x̄= 4.28, S.D. = 0.421), followed by equanimity (upekkha) which was also rated at a high level (x̄= 4.26, S.D. = 0.480). The aspect with the lowest mean score was loving-kindness (metta); however, it was still rated at a high level (x̄= 4.21, S.D. = 0.509). 2. The comparison about the opinions of school administrators and teachers towards personnel administration based on the Four Sublime States of Mind found that the opinions did not differ when classified by different gender and educational background, while there was statistically significant difference at the .05 level when comparing with different age and work experience, overall. 3. The development of personnel administration based on the Four Sublime States of Mind should focus on systematic development by adhering to the principle of loving-kindness to nurture and provide comprehensive personnel development. To aid and alleviate suffering of personnel should be complied with by using principle of compassion while principle of sympathetic joy principle should be used to promote recognition, appreciation and positive motivation, and equanimity principle should be applied for far decision- making, transparency and accountability.